(untitled) (The Research of Medical Science Review, 2025)
Background: Acute kidney injury (AKI) in cholestasis and cirrhosis patients is often caused by cholemic nephropathy which is not yet well recognized. The condition comes from damage to the tubules by bile acid and bilirubin, causing the kidneys to work less effectively. Objectives: to determine how common cholemic nephropathy is, what clinical signs it causes and what effect it has on the kidneys in people with acute kidney injury. Study Design: A Prospective Cross-sectional Study. Place and Duration of study: From April 2024 to September 2024 General Medicine Department, Sandeman Provincial Hospital / Bolan Medical College / Hospital, Quetta. Methods: this prospective cross-sectional study took place at a tertiary care hospital. KDIGO-defined cases of AKI seen in patients with cirrhosis or cholestasis were included in the study. We gathered demographic, biochemical and urine microscopy data. Where necessary, bile cast nephropathy was confirmed by doing a renal biopsy. Results: our study examined cirrhosis or cholestasis and AKI cases in 100 patients. Patients in the study were on average 52.6 years old, with a standard deviation of 11.4 years. Cholemic nephropathy was found in 38% of cases and bile casts showed up on urine microscopy in 29% and were confirmed by biopsy in 6 cases. Mean serum bilirubin was considerably higher in CN than in non-CN patients (14.2 ± 5.6 mg/dL and 8.1 ± 3.9 mg/dL; p = 0.003). Obstructive jaundice and decompensated cirrhosis were both linked to more frequent occurrence of CN. Patients in the CN group had a slightly higher rate of dying; however, it wasn’t enough to be statistically relevant. Conclusion: Patients with severe cholestasis and cirrhosis may find that cholemic nephropathy can cause AKI and, luckily, this can sometimes be reversed. Using urine microscopy and watching bilirubin levels can help doctors manage the disease well and improve kidney health.